220k views
0 votes
The expression sinx(cscx-cotx cosx) can be simplified to

User Realkes
by
5.7k points

2 Answers

0 votes
sin x and csc x are reciprocals, so sin x ( csc x) = 1.

Next:

sin x -cos x
------ * ----------- * cos x = - (cos x)^2
1 sin x

Then we have 1 - (cos x)^2, which in turn is equal to (sin x)^2 (answer)
User Pavan Kumar Varma
by
5.5k points
7 votes

Answer:

The expression sinx(cscx-cotx cosx) can be simplified to sin²x.

Explanation:

Consider the provided trigonometric expression.


sinx(cscx-cotx cosx)

Open the parentheses and apply the distributive property: a(b+c)=ab+ac


sinx\cdot cscx-cotx \cdot cosx \cdot sinx

Now use the identity:
cscx= (1)/(sinx), cotx=(cosx)/(sinx)


sinx\cdot (1)/(sinx)-(cosx)/(sinx) \cdot cosx \cdot sinx


1-cos^2x

Use the identity: 1 - cos²x = sin²x

Thus,
1-cos^2x=sin^2x

Hence the expression sinx(cscx-cotx cosx) can be simplified to sin²x.

User Gvl
by
5.8k points